Developing new analysis functions for a translational research platform: Extending the cBioPortal for cancer genomics - Unberath, Philipp; Knell, Christian; Prokosch, Hans-Ulrich; Christoph, Jan (Proceedings of the EFMI 2019 Special Topic Conference, 2019)
Background: The cBioPortal is a prevalent open-source translational research platform, allowing private instances and extensions. Objective: Our aim was to build up an own instance of cBioPortal, identify missing functionality by interviewing researchers, and implementing these extensions. Methods: We examined the code base of the cBioPortal and conducted a requirements analysis with researchers. Then an own extension was implemented and a usability evaluation was performed. Results: We developed a new tab in the results view of cBioPortal adding the option to analyze the correlation of gene expression and mutation patterns. Conclusion: While extending the cBioPortal is possible, there are still some challenges to overcome. A plug-in concept and a more detailed documentation would greatly facilitate the development of own extensions.
CRIS-Team Scopus Importer:2019-05-09
Keywords: cBioPortal; Genomics; MI-I; MIRACUM; Translational research